2016
DOI: 10.3390/mi7100192
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Efficient Wafer-Level Capping for MEMS and Imaging Sensors by Adhesive Wafer Bonding

Abstract: Device encapsulation and packaging often constitutes a substantial part of the fabrication cost of micro electro-mechanical systems (MEMS) transducers and imaging sensor devices. In this paper, we propose a simple and cost-effective wafer-level capping method that utilizes a limited number of highly standardized process steps as well as low-cost materials. The proposed capping process is based on low-temperature adhesive wafer bonding, which ensures full complementary metal-oxide-semiconductor (CMOS) compatibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…(2) adopting buried conductors created by diffusion under a layer of epitaxial silicon to avoid the height difference in the anodic bonding [6]; (3) using the thick solder (or polymer) layer to compensate height differences between metal lines and bonding rings in the solder [7] (or polymer [8]) bonding. However, choosing a thick Au layer not only requires a complex electroplating process but also instead results in the serious delamination effect at bonding rings for Au-Si bonding [9].…”
Section: Introductionmentioning
confidence: 99%
“…(2) adopting buried conductors created by diffusion under a layer of epitaxial silicon to avoid the height difference in the anodic bonding [6]; (3) using the thick solder (or polymer) layer to compensate height differences between metal lines and bonding rings in the solder [7] (or polymer [8]) bonding. However, choosing a thick Au layer not only requires a complex electroplating process but also instead results in the serious delamination effect at bonding rings for Au-Si bonding [9].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid bouncing back, the over-damping condition of RF MEMS switches is required in device packages and thus can be realized by regulating the cap cavity depth. (8) In addition, it is identified that MEMS resonators' quality factors of packaged ones (under atmospheric pressure) are smaller than those of unpackaged ones owing to squeeze film damping from cap and substrate cavities, (9) which is similarly reported in studies on MEMS switches (10) and energy harvesters. (11,12) Also, some studies indicate that the squeeze film damping coefficient of MEMS resonators decreases with increasing cavity depth, e.g., in the MEMS rotary motors (13) and scanners.…”
Section: Introductionmentioning
confidence: 65%
“…Therefore, the package must offer encapsulation with a low gas leak rate in an inert ambient gas, such as nitrogen, at atmospheric pressure to ensure the long-term stability and reliability of the MEMS switches. To solve these problems, the packaging is preferably implemented on a wafer level prior to die singulation, which is known as the wafer-level package method [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%